Sport and training influence bone and body composition in women collegiate athletes - Carbuhn, A. F.; Fernandez, T. E.; Bragg, A. F.; Green, J. S.; Crouse, S. F. (The Journal of Strength and Conditioning Research, 2010)
This is a novel descriptive study to characterize off-season, preseason, and postseason bone and body composition measures in women collegiate athletes. From 2006 through 2008, 67 women collegiate athletes from 5 sports, softball (n = 17), basketball (n = 10), volleyball (n = 7), swimming (n = 16), and track jumpers and sprinters (n = 17) were scanned using dual energy X-ray absorptiometry (DXA) at 3 seasonal periods: (a) off-season = before preseason training, (b) preseason = after preseason training, and (c) postseason = after competitive season. Dual energy X-ray absorptiometry scans were analyzed for total body mass, lean mass (LM), fat mass (FM), percent body fat (%BF), bone mineral content, bone mineral density (BMD), arm BMD, leg BMD, pelvis BMD, and spine BMD. Data were analyzed between sports using analysis of variance (ANOVA) with Tukey post hoc follow-ups, and within each sport using repeated-measures ANOVA and LSD; a < 0.05. Significant off-season to preseason or postseason changes in %BF, LM, and BMD within each sport were as follows, respectively: softball, -7, +4, +1%; basketball, -11, +4, +1%; volleyball, unchanged, unchanged, +2%; swimming, unchanged, +2.5%, unchanged; track jumpers and sprinters, -7, +3.5, +1%. Comparisons among athletes in each sport showed bone measurements of swimmers averaged 4-19% lower than that of athletes in any other sport, whereas for track jumpers and sprinters, %BF and FM averaged 36 and 43% lower compared with other sports at all seasonal periods. Values for athletes playing basketball and volleyball were most similar, whereas softball athletes' values fell between all other athletes. These data serve as sport-specific reference values for comparisons at in-season and off-season training periods among women collegiate athletes in various sports.